Implementación de la metodología de mejora 5s en la línea de producción de cuadernos universitaríos en una industria de artes gráfica - Viteri Miranda, Víctor (2010)
To compete in the current market, the companies have to learn how to be more efficient and to concentrate on eliminating the I waste in all their processes. A tool that helps to achieve this made is the methodology 5S, which teaches to the employees to have conscience of the I waste in everything that they make, improving the security and the work flow, allowing at the same time to manage the process like a better everything. The development of this project understands in first instance the justification of the selection of the methodology 5s as tool of continuous improvement. Then an analysis of the current situation of the line is made to determine the flow of the processes, to evidence the problems and to analyze the level of 5s that is presented. Later on the implementation of this methodology is detailed, that is to say the carried out activities are described, the investment of resources during the stages of planning, implementation and evaluation of the project. Finally the conclusions and recommendations are presented that synthesize all the information obtained along the implementation showing the obtained benefits and the evolution of the established indicators.